Catalase and Ascorbate Peroxidase in Euglenozoan Protists - Skodova-Sverakova, Ingrid; Zahonova, Kristina; Buckova, Barbora; Fussy, Zoltan; Yurchenko, Vyacheslav; Lukeš, Julius (MDPI AG, 2020)
In this work, we studied the biochemical properties and evolutionary histories of catalase (CAT) and ascorbate peroxidase (APX), two central enzymes of reactive oxygen species detoxification, across the highly diverse clade Eugenozoa. This clade encompasses free-living phototrophic and heterotrophic flagellates, as well as obligate parasites of insects, vertebrates, and plants. We present evidence of several independent acquisitions of CAT by horizontal gene transfers and evolutionary novelties associated with the APX presence. We posit that Euglenozoa recruit these detoxifying enzymes for specific molecular tasks, such as photosynthesis in euglenids and membrane-bound peroxidase activity in kinetoplastids and some diplonemids.
Keywords: Euglenozoa; ascorbate peroxidase; catalase; enzymatic activity; phylogeny